Spatial Scenarios and the Lisbon Strategy - Ed Dammers; David Evers; Aldert De Vries (European Regional Science Association (ERSA), 2005)
The European Union is changing significantly. It has recently been enlarged by 10 new Member States, decision-making about the European Constitution is going on, and it has set itself the target of becoming the most competitive economy in the world (Lisbon Strategy). The scenarios explore in an integrated way the territorial impacts of future changes in the economy, transport, rural development, environment, and other policy fields. They do not only concentrate on the territorial impacts of the trends and driving forces but also of the relevant EU Policies. The scenarios throw a light on the effectiveness of EU Policies and the synergies as well as conflicts they generate. By doing this they provide important insights in the conditions under which these trends, driving forces and policies will favour a balanced and polycentric territory and territorial cohesion within the enlarging European Union. These insights are relevant for recommendations on possible adjustments and/or changes of EU Policies.
Keywords: 330